2017
DOI: 10.1007/s12639-017-0931-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pathogenic parasite Histomonas meleagridis in poultry in Lorestan province, western Iran

Abstract: is a flagellate protozoan parasite living in the cecum of birds digestive system and is the causative agent of histomoniasis. In this study 110 poultry fresh stool samples were assessed in order to detect , and egg or adult worm of in Lorestan province, Iran. The results showed that the prevalence of was 31%. Also, 19.5% of infected poultry had a watery stool. The eggs or adult worms of were not seen in any of the samples. The results showed the high prevalence of this parasite, and the factors such as tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…All samples were transported the same day of collection in a pre-cooled portable fridge to the laboratory for immediate processing and analysis. For parasite identification and assessment of infection frequency, we used the formol-ether technique (Larki et al 2018 ), followed by staining of slides with Lugol (Badparva and Kheirandish 2017 ). All samples were examined under a light microscope and representative photographs were taken for the subsequent identification of the parasites based on their morphological characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were transported the same day of collection in a pre-cooled portable fridge to the laboratory for immediate processing and analysis. For parasite identification and assessment of infection frequency, we used the formol-ether technique (Larki et al 2018 ), followed by staining of slides with Lugol (Badparva and Kheirandish 2017 ). All samples were examined under a light microscope and representative photographs were taken for the subsequent identification of the parasites based on their morphological characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, it was believed that infection with Histomonas meleagridis (H. meleagridis) primarily resulted from eating Histomonas gallinarum (H. gallinarum) eggs, either directly or through earthworms harboring these eggs (Patra et al, 2013). However, recent studies have increasingly reported H. meleagridis infections without the presence of nematodes (Badparva and Kheirandish, 2017). Recently, researchers have widely explored alternative modes of chicken infection, specifically highlighting transmission through the mouth and cloaca.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism allows pathogens to penetrate the caecum and bursa of Fabricius (Sorvari and Sorvari, 1977;Huber et al, 2006;Patra et al, 2013). This mode of infection has been identified as a risk factor for the dissemination of H. meleagridis via the cloaca (Huber et al, 2006, Badparva andKheirandish, 2017).…”
Section: Introductionmentioning
confidence: 99%